Redox Systemic Signaling and Induced Tolerance Responses During Soybean–Bradyrhizobium japonicum Interaction: Involvement of Nod Factor Receptor and Autoregulation of Nodulation - Fernandez-Göbel, Tadeo F.; Deanna, Rocío; Muñoz, Nacira B.; Robert, Germán; Asurmendi, Sebastian; Lascano, Ramiro (Frontiers in Plant Science, 2019)
The symbiotic relationship between legumes and nitrogen-fixing rhizobia induces local and systemic responses, which ultimately lead to nodule formation. The Autoregulation of Nodulation (AON) is a systemic mechanism related to innate immunity that controls nodule development and involves different components ranging from hormones, peptides, receptors to small RNAs. Here, we characterized a rapid systemic redox changes induced during soybean-Bradyrhizobium japonicum symbiotic interaction. A transient peak of reactive oxygen species (ROS) generation was found in soybean leaves after 30 min of root inoculation with B. japonicum. The ROS response was accompanied by changes in the redox state of glutathione and by activation of antioxidant enzymes. Moreover, the ROS peak and antioxidant enzyme activation were abolished in leaves by the addition, in either root or leaf, of DPI, an NADPH oxidase inhibitor. Likewise, these systemic redox changes primed the plant increasing its tolerance to photooxidative stress. With the use of non-nodulating nfr5-mutant and hyper-nodulating nark-mutant soybean plants, we subsequently studied the systemic redox changes. The nfr5-mutant lacked the systemic redox changes after inoculation, whereas the nark-mutant showed a similar redox systemic signaling than the wild type plants. However, neither nfr5- nor nark-mutant exhibited tolerance to photooxidative stress condition. Altogether, these results demonstrated that i) the early redox systemic signaling during symbiotic interaction depends on a Nod factor receptor, and that ii) the induced tolerance response depends on the AON mechanisms.